Linking voice pitch to fighting success in male amateur mixed martial arts athletes and boxers. (10th September 2021) - Schild, Christoph; Zettler, Ingo
Abstract: Abstract: Whereas voice pitch is strongly linked to people's perceptions in contexts of sexual selection, such as attractiveness and dominance, evidence that links voice pitch to actual behaviour or the formidability of a speaker is sparse and mixed. In this registered report, we investigated how male speakers' voice pitch is linked to fighting success in a dataset comprising 135 (amateur) mixed martial arts and 189 (amateur) boxing fights. Based on the assumption that voice pitch is an honest signal of formidability, we expected lower voice pitch to be linked to higher fighting success. The results indicated no significant relation between a fighter's voice pitch, as directly measured before a fight, and successive fighting success in both mixed martial arts fighters and boxers.